Environmental factors affecting Macrocephalon maleo presence in nesting habitats of Lore Lindu National Park, Indonesia - RINA FATKHIYAH; SANDY NURVIANTO; SENA ADI SUBRATA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Fatkhiyah R, Nurvianto S, Subrata SA. 2026. Environmental factors affecting Macrocephalon maleo presence in nesting habitats of Lore Lindu National Park, Indonesia. Biodiversitas 27 (4): d270431. https://doi.org/10.13057/biodiv/d270431. Macrocephalon maleo, commonly known as the maleo, is a critically endangered bird endemic to Sulawesi, recognized for its distinctive nesting strategy of burying eggs in geothermally or solar-heated soil. This study examined nesting habitat characteristics and environmental factors influencing its presence in Lore Lindu National Park (LLNP), Central Sulawesi, Indonesia. From June 2024 to February 2025, field surveys and camera trap monitoring were conducted at 27 nesting sites. Active nesting grounds were primarily located on gentle slopes from lowland to lower montane forests, which associated with sandy soils near geothermal sources. Soil temperature at nesting sites ranged from 25 to 41°C. Canopy cover ranged from 24-88%, while understory cover ranged from 46-89%. Logistic regression analysis indicated that understory vegetation cover was the only variable significantly associated with maleo presence (p-value: 0.00997), with higher understory cover corresponding to lower occurrence. Other measured environmental variables showed no significant relationship with maleo presence, indicating that soil and thermal conditions across nesting sites met the species’ nesting requirements, whereas understory structure directly influenced nesting accessibility and predator detection. These results demonstrate that maleos select nesting habitats with open ground conditions. Conservation management should therefore prioritize the maintenance of open understory structure and the protection of confirmed active nesting grounds. This study was limited to a single-season observational design and did not address interannual variation in nesting activity. The findings provide quantitative ecological evidence to support habitat-based conservation of maleo populations in LLNP and Sulawesi.